Potentiometric Glucose Detection by Paper-based Electrochemical Sensor on CMOS Chip - Katsuyuki Yamaoka; Jun Eguchi; Shigeyasu Uno (Universitas Ahmad Dahlan, 2017)
This paper presents a low cost portable medical device for biochemical sensor using CMOS chip and paper-based fluidic channel. We measured a potential produced by enzyme activity of glucose between the working and reference electrode on CMOS chip. A liquid sample is transported by paper-based fluidic channel, which is made of chromatography paper and silicone resin, and consists of the area for filtering a sample (filter layer) and that for reacting enzyme (enyzme layer). The paper-based fluidic channel is used by combining CMOS chip, and the solution with glucose is dropped from top of the paper-based fluidic channel. The concentrations of glucose are detected by potentiometry (open circuit potential time). The experimental results show that the glucose concentration is measured by CMOS chip and paper-based fluidic channel.